Collaborative Governance in Optimizing State Revenue through Customs Facilities in the Sanur Special Economic Zone - Ah Farid Nurrohman; Luh Putu Mahyuni (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: The Sanur Special Economic Zone (SEZ) is a strategic government initiative that integrates health services, tourism, and investment activities. The provision of customs facilities in SEZs provides investment incentives but also creates potential fiscal risks that require accountable governance and effective supervision. Therefore, collaborative governance is essential to ensure that fiscal facilities support economic growth while maintaining state revenue protection. Objective: This study aims to analyze collaborative governance practices in managing customs facilities at the Sanur SEZ and identify factors influencing the optimization of potential state revenue. Methods: This study employed a qualitative case study approach. Data were collected through document analysis, micro-evaluation reports of Sanur SEZ, performance evaluation reports, special monitoring reports, focus group discussions, interviews, and regulatory reviews. Data were analyzed using Ansell and Gash’s collaborative governance framework, focusing on dialogue, trust building, commitment, shared understanding, and intermediate outcomes. Results: The findings indicate that customs facilities function as both investment incentives and fiscal supervision instruments. Collaboration among government institutions, SEZ administrators, and business actors has contributed to increased investment, employment, facility utilization, and monitoring effectiveness. However, challenges remain in system integration, IT Inventory implementation, regulatory consistency, and compliance. Special monitoring identified potential revenue recovery through import duty and tax collection recommendations totaling IDR 813,129,741. Conclusion: Strengthening collaborative governance through digital integration, transparency, and continuous evaluation is crucial to optimizing state revenue while maintaining investment competitiveness in the Sanur SEZ.